2008
DOI: 10.1111/j.1467-9450.2008.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of skin tone, hair length, and hair colour on ratings of women's physical attractiveness, health and fertility

Abstract: The present study investigated the role of skin tone, hair colour and hair length in perceptions of women's physical attractiveness, health and fertility. One-hundred and thirty men and 112 women rated a series of 12 line drawings that varied in three levels of skin tone, two levels of hair colour and two levels of hair length. Results showed a number of interactions between the three variables, suggesting that these phenotypes are highly intercorrelated. However, there were also significant main effects of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 34 publications
3
52
3
Order By: Relevance
“…Moreover, Sorokowski (2008) showed that men judged images of women with (digitally-enhanced) blonde hair significantly younger than the same images with brown hair (particularly in women around the age of 30). This result is, however, in contrast to the findings of Swami and Furnham (2007), who reported that blondes were rated as less physically attractive and more promiscuous than brunettes, a result that was replicated in two follow-up studies by the same authors (Swami et al, 2008a,b). …”
Section: Introductioncontrasting
confidence: 62%
“…Moreover, Sorokowski (2008) showed that men judged images of women with (digitally-enhanced) blonde hair significantly younger than the same images with brown hair (particularly in women around the age of 30). This result is, however, in contrast to the findings of Swami and Furnham (2007), who reported that blondes were rated as less physically attractive and more promiscuous than brunettes, a result that was replicated in two follow-up studies by the same authors (Swami et al, 2008a,b). …”
Section: Introductioncontrasting
confidence: 62%
“…This was done to further explore whether using lower WHRs than what has been commonly used so far (0.7, 0.8, 0.9, and 1.0) would significantly affect attractiveness ratings. In previous studies (e.g., Frost, 1988Frost, , 2007Frost, , 2008Frost, , 2011Swami, Furnham, & Joshi, 2008;van den Berghe & Frost, 1986), participants found lighter-skinned women to be more attractive. If skin tone plays a role in attractiveness, we would expect dark and light complexions to be assessed differently, as shown by eye movements and attractiveness ratings.…”
Section: Methodsmentioning
confidence: 99%
“…It follows that individual features linked to high investment in offspring (reproductive potential) and strong commitment to children wellbeing (reproductive investment) would give a selective advantage to individuals in the process of mating choice (Geary et al, 2004). The choice of partner would therefore stem from considerations about elements associated to SES and social position as well as from attraction to physical characteristics concerning facial beauty and symmetry (Thornhill and Gangestad, 1993;Cornwell et al, 2006), height (Cavelaars et al, 2000;Silventoinen, 2003), hair and eye color (Frost, 2006;Swami et al, 2008), skin color (Hulse, 1967;Frost, 1994;Aoki, 2002), and other somatic traits linked to higher fitness. Accordingly, unhealthy individuals, especially those with evident signs of illness and malformation, would be negatively selected for marriage and, consequently, excluded from the reproductive process.…”
mentioning
confidence: 98%